2014
DOI: 10.12659/msm.889989
|View full text |Cite
|
Sign up to set email alerts
|

Association between suicidal ideation and behavior, and depression, anxiety, and perceived social support in cancer patients

Abstract: BackgroundThe aim of this study was to determine the relationship between suicidal behavior and associated factors such as depression, anxiety, and perceived social support level in cancer patients.Material/MethodsThe study group included 102 patients who were under treatment in the oncology department and the control group included 100 individuals with similar sociodemographic features. A sociodemographic information form, Beck depression inventory, Beck anxiety inventory, suicidal behavior inventory, suicida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
8
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 34 publications
(38 reference statements)
7
8
0
7
Order By: Relevance
“…The higher level of perceived social support among the breast cancer subjects was associated with better QoL. This finding is similar to several previous studies [ 17 19 ]. In general, the level of perceived social support measured using MSPSS was relatively good among the subjects in the current study in comparison with the other studies [ 17 , 29 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The higher level of perceived social support among the breast cancer subjects was associated with better QoL. This finding is similar to several previous studies [ 17 19 ]. In general, the level of perceived social support measured using MSPSS was relatively good among the subjects in the current study in comparison with the other studies [ 17 , 29 ].…”
Section: Discussionsupporting
confidence: 91%
“…Instead, research has shown that it is the social support felt or perceived by the individual that produces the positive impact [ 14 16 ]. Perceived social support is negatively correlated with psychological distress and suicidal thought in cancer patients [ 17 ]. It is also associated with better orientation to health care services and adjustment to family relationship.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that our sample did not include patients with advanced stages of cancer, coupled with the lack of previous psychiatric disorders in our patients and their good functional ability may explain the lower prevalence in our study. The present study found a prevalence of suicide ideation or risk of 11.7%, − overlapping with other diagnosis-, in line with Balcı Şengül et al's results [4]. Likewise, at the end of radiotherapy, there was a decrease in the prevalence of suicide ideation or risk, with the same trend as in the mood disorders, going from the initial 11.7% to 7.8% at the end of radiotherapy, a percentage which is higher than that of the general population in Spain (3.4%) [31].…”
Section: Psychopathological Disorders Structured Interview Mini Andsupporting
confidence: 93%
“…Mehnert et al reported a prevalence of 31.8% of psychopathological disorders in cancer patients; this included depressive disorders (6.5%), anxiety disorders (11.5%) and adjustment disorders (11.1%) [3]. Suicide ideation in cancer patients is greater than in the general population, and is thought to be around 12.3% [4]. Despite the numerous studies on psychopathology and emotional distress in cancer patients, only a small number of studies focused on the patients during treatment with radiotherapy [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also demonstrated that the suicide rate of cancer patients is twice that of general population 2, 3, 4, 5, 6. Notably, when considering different anatomic cancer sites, patients diagnosed with lung cancer had a higher suicide rate than those with other cancer, with a standardized mortality ratio of 5.74 2.…”
Section: Introductionmentioning
confidence: 99%